To find the missing value \( f(4) \) using the exponential function \( f(x) = 3(1.2)^x \), we will substitute \( x = 4 \) into the function.
\[ f(4) = 3(1.2)^4 \]
Now, we need to calculate \( (1.2)^4 \):
\[ (1.2)^4 = 1.2 \times 1.2 \times 1.2 \times 1.2 \]
Calculating this step by step:
- \( 1.2 \times 1.2 = 1.44 \)
- \( 1.44 \times 1.2 = 1.728 \)
- \( 1.728 \times 1.2 = 2.0736 \)
So,
\[ (1.2)^4 \approx 2.0736 \]
Now, we multiply by 3:
\[ f(4) = 3 \times 2.0736 \approx 6.2208 \]
Rounding this to two decimal places:
\[ f(4) \approx 6.22 \]
So the missing value in the table for \( f(4) \) is approximately 6.22.